The relevance of primary tumour location in patients with metastatic colorectal cancer: A meta-analysis of first-line clinical trials. (January 2017) - Holch, Julian Walter; Ricard, Ingrid; Stintzing, Sebastian; Modest, Dominik Paul; Heinemann, Volker
Abstract: Background: Retrospective subgroup analyses suggest that primary tumour location (PTL) has a prognostic importance and relates to response to targeted therapy. Methods: We conducted a meta-analysis of first-line clinical trials available up to October 2016, which assessed the relevance of PTL in patients with metastatic colorectal cancer (mCRC). Right- and left-sided colorectal cancers were differentiated (RC and LC). Results: In 13 first-line randomised controlled trials and one prospective pharmacogenetic study, RC was associated with a significantly worse prognosis compared with LC (hazard ratio [HR] for overall survival: 1.56; 95% confidence interval [CI]: 1.43–1.70; P < 0.0001). A meta-analysis of PRIME and CRYSTAL study suggests that PTL was predictive of survival benefit from addition of anti-EGFR antibody to standard chemotherapy in patients with RAS wild-type tumour (overall survival, HR for LC: 0.69; 95% CI: 0.58–0.83; P < 0.0001 and HR for RC: 0.96; 95% CI: 0.68–1.35; P = 0.802). A meta-analysis of FIRE-3/AIO KRK0306, CALGB/SWOG 80405 and PEAK study indicates that patients with RAS wild-type LC had a significantly greater survival benefit from anti-EGFR treatment compared with anti-VEGF treatment when added to standard chemotherapy (HR 0.71; 95% CI: 0.58–0.85; P = 0.0003). By contrast, in patients with RC, benefit from standard therapy was poor and bevacizumab-based treatment was numerically associated with longer survival (HR 1.3; 95% CI: 0.97–1.74; P = 0.081). Conclusions: The present meta-analysis demonstrates that PTL is prognostic in mCRC. Further, it supports the conclusion that patients with left-sided RAS wild-type mCRC should be preferentially treated with an anti-EGFR antibody. In right-sided mCRC, chemotherapy plus bevacizumab is a treatment option, but optimal treatment has yet to be defined.